Acute and chronic cognitive effects of levodopa and dopamine agonists on patients with Parkinson's disease: a review. (April 2013) - Poletti, Michele; Bonuccelli, Ubaldo
The spatiotemporal progression of dopamine depletion in Parkinson's disease (PD) provides a special model for assessing dopaminergic effects on neural systems with differential baseline dopamine levels. This study aims at reviewing cognitive effects of dopaminergic stimulation in PD. While considering dopaminergic drugs (levodopa or dopamine agonists), temporal intervals (acute or chronic) and cognitive domains, we found that empirical evidence was almost focused on acute effects of levodopa on executive functions. The paucity of empirical evidence suggests that no meaningful conclusions can be actually drawn and further research is needed in relation to: (1) other cognitive domains; (2) the acute cognitive effects of dopamine agonists, as compared with levodopa; (3) possible differences between cognitive effects of different dopamine agonists; (4) the cognitive effects of chronic dopaminergic therapies. The latter issue is of particular clinical interest considering that many PD patients present a mild cognitive impairment: is this cognitive feature worsened or improved by the prolonged dopaminergic therapy? In addition to the potential risk of inducing dyskinesia and behavioral side effects such as impulse control disorders, also cognitive effects of prolonged dopaminergic treatments should be taken in account by clinicians in order to anticipate or to delay their prescription to PD patients.